Generation of β cell‐specific human cytotoxic T cells by lentiviral transduction and their survival in immunodeficient human leucocyte antigen‐transgenic mice. (March 2015) - Babad, J.; Mukherjee, G.; Follenzi, A.; Ali, R.; Roep, B. O.; Shultz, L. D.; Santamaria, P.; Yang, O. O.; Goldstein, H.; Greiner, D. L.; DiLorenzo, T. P.
Summary Several β cell antigens recognized by T cells in the non‐obese diabetic (NOD) mouse model of type 1 diabetes (T1D) are also T cell targets in the human disease. While numerous antigen‐specific therapies prevent diabetes in NOD mice, successful translation of rodent findings to patients has been difficult. A human leucocyte antigen (HLA)‐transgenic mouse model incorporating human β cell‐specific T cells might provide a better platform for evaluating antigen‐specific therapies. The ability to study such T cells is limited by their low frequency in peripheral blood and the difficulty in obtaining islet‐infiltrating T cells from patients. We have worked to overcome this limitation by using lentiviral transduction to 'reprogram' primary human CD8 T cells to express three T cell receptors (TCRs) specific for a peptide derived from the β cell antigen islet‐specific glucose‐6‐phosphatase catalytic subunit‐related protein (IGRP265–273) and recognized in the context of the human class I major histocompatibility complex (MHC) molecule HLA‐A2. The TCRs bound peptide/MHC multimers with a range of avidities, but all bound with at least 10‐fold lower avidity than the anti‐viral TCR used for comparison. One exhibited antigenic recognition promiscuity. The β cell‐specific human CD8 T cells generated by lentiviral transduction with one of the TCRs released interferon (IFN)‐γ in response to antigen and exhibited cytotoxic activity against peptide‐pulsed target cells. The cells engrafted in HLA‐A2‐transgenic NOD‐scid IL2rγnull mice and could be detected in the blood, spleen and pancreas up to 5 weeks post‐transfer, suggesting the utility of this approach for the evaluation of T cell‐modulatory therapies for T1D and other T cell‐mediated autoimmune diseases.